TOPIKALISASI DAN BENTUK WACANA KESEHATAN PADA KORAN SURYA JANUARI 2019 - Endah Sari (STKIP PGRI Jombang, 2019)
This research focuses on topicalisation and forms of discourse contained in the health discourse in the January 2019 edition of Surya newspaper. The description underlying the researcher conducted this study is using discourse analysis as the main theoretical basis and the basis of research, beside topicalisation and discourse form as the subjects in research. The objectives of this study are to describe the topics between sentences and to know health discourse form. Descriptive approach is used in this research. The type of data examined at the focus of the first problem is sentence in each the health discourse’s paragraph in the January 2019 edition of Surya newspaper and the type of data examined at the focus of the first problem is the paragraphs in the discourse. The data collection techniques are observation, deciding the object, identifying data and coding data. Based on the problem, to have a data validity test, the researcher uses triangulation theory which compares the final result as information with relevant theory perspective to avoid researcher’s individual biases of the finding produced. The result of the study shows that not all paragraphs in the discourse have the topic. However, whole discourses have each main topic. In the research of discourse form, the result of analysis shows that expository discourse is the most frequent delivered in the health discourse in the January 2019 edition of Surya newspaper. There are hortatory discourse forms in the health discourse in the January 2019 edition of Surya newspaper, but not as much as expository discourse. Narrative discourse form is a most rarely delivered. Procedural discourse form, dramatic discourse, epistolary discourse and ceremonial discourse are not found in the health discourse in the January 2019 edition of Surya newspaper.